Study on the relationship between MYCN status and certain prognostic factors in 131 patients with neuroblastoma - Vu, Dinh Quang; Phung, Tuyet Lan; Pham, Duy Hien; Le, Dinh Cong; Hoang, Ngoc Thach; Tran, Thi Chi Mai; Nguyen, Xuan Huy; Ngo, Diem Ngoc; Nguyen, Thi Hong Van (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2016)
Neuroblastoma (NBL) is the most common extracranial solid cancer of childhood and is characterized by a remarkable biological heterogeneity, resulting in favorable or unfavorable outcomes. There are many prognostic factors like age, stage, histopathology, plasma and urinary markers and the molecular characteristics of tumor cells. Amplification of the MYCN gene (MYCNA) is established as the most powerful prognostic factor. This study aimed to investigate, in a series of 131 NBL patients ascertained from 2013 to 2015, the relationship between amplification of MYCN and some other prognostic factors: patient’s age, histopathology, VMA/HVA ratio and LDH level. MYCNA was identified by FISH and the MYCN status was compared with the other clinic-biological factors. As a result, MYCNA was found on 27/131 NBL patients. The number of MYCNA according to the age group was 9/27 cases below12 months, 4/27 cases 12- 18 months and 14/27 cases over 18 months. The favorable and unfavorable histology cases showed a different frequency of MYCNA, 11/24 cases and 13/24 cases, respectively. 20/21 patients with MYCNA have a VMA/HVA ratio below 1, and 17/24 cases of them had LDH level above three times than normal level (both associated with worse prognosis). Therefore, the MYCNA is strongly associated with age at diagnosis >18 months, unfavorable histology, VMA/HVA ratio below 1 and high LDH level. The VMA/HVA ratio and LDH level could be valuable markers for diagnosis and monitoring of disease status, however, the MYCN status determined by FISH is one of the most important tools for treatment stratification.